Identify the CAPM and company return to determine efficient or non-efficient in the Business Support Services Industry - putri, riau setyaning; Heikal, Jerry (Journal of Entrepreneurship, Management and Industry (JEMI), 2024)
Investment is an effective way to develop wealth and long-term financial goals, so investors must make the right decisions for the shares that want to be managed in order to get profitable returns. In making investment decisions, investors must consider various factors such as market conditions, company performance, and economic trends. The objectives of this research are: (1) To help investors choose efficient and inefficient stocks, (2) Investors know the stocks that have optimal returns and appropriate risks, (3) Investors learn about CAPM methods in determining the best investment decisions. A CAPM is a model for estimating the rate of return obtained from risk securities or as a measure in evaluating the return rate of an investment. The population in this study is a company listed on the Indonesian Stock Exchange, i.e. with sub-industry shares of Business Support Services. These stocks are Astra Graphia Tbk (ASGR), Dyandra Media International Tbk (DYAN), Island Concepts Indonesia Tbk (ICON), and Multifiling Partners Indonesia Tbk (MFMI). The selection criterion in this study is to select efficient stocks where individual return rate > expected return rate Ri>E(Re). Efficient stock collection should be a priority in investment decisions, only efficient shares can be purchased. The results of this research show that: There are 1 shares that are efficient in the business support services industry sector namely ASGR. These shares have a value of Ri>E(Re), the investment decision that must be taken by the investor is to buy efficient shares. Based on data analysis, there is a non-linear relationship between systematic risk and expected share returns.